Comparison of the Effect of Three Cements on Prevention of Enamel Demineralization Adjacent to Orthodontic Bands - Mehdi Kashani; Sareh Farhadi; Neda Rastegarfard (Tabriz University of Medical Sciences, 2012)
Background and aims. This in vitro study was designed to compare enamel demineralization depths adjacent to bands cemented with zinc polycarboxylate, glass ionomer (GI) and resin-modified glass ionomer (RMGI), in order to achieve minimal enamel demineralization during orthodontic treatment. Materials and methods. Sixty fully developed extracted third molars were randomly divided into three test groups each containing 20 samples, used to cement orthodontic bands with zinc polycarboxylate, GI and RMGI. All samples were demineralized using White method using hydroxyapatite, latic acid and Carbapol for in vitro caries simulation, and then, immersed in 10% solution of methylene blue. The mean depth of dye penetration was assessed up to 0.1 millimeter, reflecting the depth of enamel demineralization. One way ANOVA and LSD statistical tests were employed to evaluate significant differences among groups. Results. The highest dye penetration depth was seen in zinc polycarboxylate group, followed by GI, and RMGI groups, respectively, with significant differences among each two groups (P < 0.05). Conclusion. The use of RMGI cement seems to present significantly better prevention of enamel demineralization adjacent to orthodontics bands.